Partial deletion of the αC-domain in the Fibrinogen Perth variant is associated with thrombosis, increased clot strength and delayed fibrinolysis - Westbury, Sarah K.; Duval, Cédric; Philippou, Helen; Brown, Rebecca; Lee, Kurtis R.; Murden, Sherina L.; Phillips, Emma; Reilly-Stitt, Christopher; Whalley, Daniel; Ariëns, Robert A.; Mumford, Andrew D. (Thrombosis and Haemostasis, 2013)
Genetic fibrinogen (FGN) variants that are associated with bleeding or thrombosis may be informative about fibrin polymerisation, structure and fibrinolysis. We report a four generation family with thrombosis and heritable dysfibrinogenaemia segregating with a c.[1541delC];[=] variation in FGA (FGN-Perth). This deletion predicts a truncated FGN αC-domain with an unpaired terminal Cys at residue 517 of FGN-Aα. In keeping with this, SDS-PAGE of purified FGN-Perth identified a truncated FGN-Aα chain with increased co-purification of albumin, consistent with disulphide bonding to the terminal Cys of the variant FGN-Aα. Clot visco-elastic strength in whole blood containing FGN-Perth was greater than controls and tPA-mediated fibrinolysis was delayed. In FGN-Perth plasma and in purified FGN-Perth, there was markedly reduced final turbidity after thrombin-mediated clot generation. Consistent with this, FGN-Perth formed tighter, thinner fibrin fibres than controls indicating defective lateral aggregation of protofibrils. Clots generated with thrombin in FGN-Perth plasma were resistant to tPA-mediated fibrinolysis. FGN-Perth clot also displayed impaired tPA-mediated plasmin generation but incorporated α2-anti-plasmin at a similar rate to control. Impaired fibrinolysis because of defective plasmin generation potentially explains the FGN-Perth clinical phenotype. These findings highlight the importance of the FGN αC-domain in the regulation of clot formation and fibrinolysis.
Keywords: Dysfibrinogenaemia; thrombosis; fibrin polymerisation; fibrinolysis